2018
DOI: 10.1039/c7sm02357j
|View full text |Cite
|
Sign up to set email alerts
|

Overcharging and reentrant condensation of thermoresponsive ionic microgels

Abstract: We investigated the complexation of thermoresponsive anionic poly(N-isopropylacrylamide) (PNiPAM) microgels and cationic ε-polylysine chains. We show that the volume phase transition of the microgels triggers polyion adsorption and gives rise to a thermosensitive microgel overcharging and reentrant condensation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(66 citation statements)
references
References 83 publications
13
52
1
Order By: Relevance
“…The trend can be rationalised by thinking of the microgels only in physical terms (ignoring polymer-solvent interactions which are not yet dominant): as the particles become smaller, they also become more compact and hence somewhat less penetrable. A further change in interactions at high T is however hinted by the present results, as the simple repulsive model that we have adopted shows increasing deviations at the highest studied T = 30 • C, approaching the VPTT at 32 • C. Close to the VPTT, a much more careful evaluation, also in terms of charge effects which could become important as shown by our and others preliminary measurements [43], will be required. For the examined T -interval, the present findings clearly show that the variation of volume fraction that is obtained by changing T , a commonly used method in experiments to efficiently explore a larger portion of the phase diagram, should be done with caution, as doing so significantly affects the effective interactions between the particles.…”
Section: Discussionsupporting
confidence: 53%
“…The trend can be rationalised by thinking of the microgels only in physical terms (ignoring polymer-solvent interactions which are not yet dominant): as the particles become smaller, they also become more compact and hence somewhat less penetrable. A further change in interactions at high T is however hinted by the present results, as the simple repulsive model that we have adopted shows increasing deviations at the highest studied T = 30 • C, approaching the VPTT at 32 • C. Close to the VPTT, a much more careful evaluation, also in terms of charge effects which could become important as shown by our and others preliminary measurements [43], will be required. For the examined T -interval, the present findings clearly show that the variation of volume fraction that is obtained by changing T , a commonly used method in experiments to efficiently explore a larger portion of the phase diagram, should be done with caution, as doing so significantly affects the effective interactions between the particles.…”
Section: Discussionsupporting
confidence: 53%
“…Though since the pioneering work of Pelton and co-workers [ 30 ], a large increase of microgel electrophoretic mobility is known to exist above the volume phase transition temperature of the microgels due to the ionic initiators anchored to the polymer network, PNIPAm microgels have been often considered as neutral colloids, since their inner structure does not contain ionizable monomers. Only very recently few works pointed out that the residual charge borne by PNIPAm microgels synthesized via FRP can affect their behavior in aqueous media [ 31 , 32 ] and in presence of oppositely charged polymers [ 32 ]. Whether PNIPAm microgels synthesized via FRP behave like neutral colloids in water and how their VPT affects their electrostatics are still debated issues.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work [ 32 ] we have shown that PNIPAm microgels can electrostatically adsorb short polylysine polymers, that the amount of adsorbed polymer largely increases above the VPT and that such an adsorption triggers, though only very close to the critical temperature, both microgel reentrant condensation and overcharging, two phenomena characterizing charged colloids and occurring only in the presence of particles with sufficiently high charge densities.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even those constituted by PNIPAM only (often considered as neutral microgels) show interesting features, particularly above the VPT temperature, which suggest the presence of charge effects. 10,15 In addition, microgels consisting of two different interpenetrated networks, made of PNIPAM and PAAc respectively, have recently gathered a lot of attention because of their suitability to study the problem of fragility in structural glasses. 16,17 From the theoretical point of view, several investigations of the swelling of charged microgels, mostly relying on a mean-field treatment of the polymer network based on the Flory-Rehner theory, 18 have been reported.…”
Section: Introductionmentioning
confidence: 99%